Simple moving average: the technical analysis on the KLSECI and S&P 500 / Aslinda Taslim - Taslim, Aslinda (2008)
Simple Moving Average (SMA) method is one of the Technical Analysis rules. The Technical analysis is where analyst or chartist is often used in order to predict future prices and returns. This paper empirically determined the significant return by applying this method on the Malaysia Stock Market and US market that based on indices, KLCI and S&P 500. The paper concentrated on short term period of moving average which is 20 days of parameter which generated Buy and Sell signals. This study based on the historical closing price of Kuala Lumpur Composite Index and S&P 500 for over the period of January 2003 to December 2007. This study used one tailed one sample t-test method to test the significance of the return calculated for buy and sell decisions. This study found that the SMA method is not suggested to apply on the Malaysia stock market for the reason of evidence shown that the significant for investor to leave negative returns is out of confidence level. Even though there is high significant level on positive rate of return for buying stock on the market, SMA did not successfully perform its ability to confirm the hypotheses where there is a significant negative returns if selling stocks. Nevertheless, the SMA did perform well on the US market which it was tested on S&P 500 indexes.